Upper-plate magma-poor rifted margins: Stratigraphic architecture and structural evolution. (January 2016) - Haupert, Isabelle; Manatschal, Gianreto; Decarlis, Alessandro; Unternehr, Patrick
Abstract: Although it is generally accepted that many distal, magma-poor rifted margins are asymmetric and can be divided into lower and upper plate margins, little is known about the details of how and when this asymmetry evolves and how upper and lower plate margins can be distinguished. This is due to the fact that most papers focused on the so called lower plate margins, while the upper plate margins remained less well understood, mainly due to the lack of public accessible drill hole data. The aim of this paper is to provide a first order description of the global architecture and stratigraphic evolution of an upper plate, magma-poor rifted margin. In order to provide such a template, we focused on 2 seismic sections, the ION-1000 line (East Indian margin), and the SCREECH 2 line (Newfoundland margin) and describe key, km-scale outcrops from the fossil European margin exposed in the Western/Central Alps, all of which document classical upper plate margins. Based on these data we show that upper plate magma-poor rifted margins can be characterized by a staircase type architecture with terraces (T1, T2, T3 ) and ramps (R1, R2 ) that result as a consequence of an evolution through a coupling, exhumation and breakup stage. We also defined key stratigraphic levels that we try to link with the evolution of the margin which enables us to link the tectonic evolution with the creation of accommodation space and formation of the staircase architecture that characterizes the upper plate margin. From these observations we develop a conceptual model for the evolution of upper-plate margins and discuss the applicability of this model for different strain rates, rates of subsidence and sedimentation rates. Highlights: Generic model to describe architecture and evolution of upper plate magma-poor rifted margins. Linking the stratigraphic, isostatic and structural evolution during rifting. Comparison between fossil and present-day margins enables to up and down-scale observations.